The toolkit for nonparametric identification nonlinear dynamical systems based on Volterra models in frequency domain - Pavlenko, V.D.; Speranskyy, V.A. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2014)
The software-hardware tools used for nonlinear dynamical systems nonparametric identification based on Volterra models in frequency domain are presented. The polyharmonic test impacts are selected as the test ones. The proposed methodology and the toolkit are used for building the communication channel model.